2016
DOI: 10.18632/oncotarget.12379
|View full text |Cite
|
Sign up to set email alerts
|

Distinct biological effects of low-dose radiation on normal and cancerous human lung cells are mediated by ATM signaling

Abstract: Low-dose radiation (LDR) induces hormesis and adaptive response in normal cells but not in cancer cells, suggesting its potential protection of normal tissue against damage induced by conventional radiotherapy. However, the underlying mechanisms are not well established. We addressed this in the present study by examining the role of the ataxia telangiectasia mutated (ATM) signaling pathway in response to LDR using A549 human lung adenocarcinoma cells and HBE135-E6E7 (HBE) normal lung epithelial cells. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Regarding the mechanisms by which LDR preserves mitochondrial integrity, we do not have direct evidence based on the present study; however we assumed the protective effects of LDR, as illustrated in Figure 8 , most likely due to its following reasons: (1) LDR stimulates Akt and Nrf2 functions via generating small amount of ROS [ 21 , 40 ] to up-regulate multiple antioxidants or free radical scavenging capacities [ 21 , 24 , 40 ]; (2) LDR-increased expression of mitochondrial superoxide dismutase [ 41 , 42 ] which may be mediated by LDR-up-regulated Nrf2 transcription function, contributing to the resistance of cardiac cells to DOX; (3) LDR-stimulated mitogen activated protein kinase that turn on cell survival signaling in normal tissues, but not in tumor tissue [ 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the mechanisms by which LDR preserves mitochondrial integrity, we do not have direct evidence based on the present study; however we assumed the protective effects of LDR, as illustrated in Figure 8 , most likely due to its following reasons: (1) LDR stimulates Akt and Nrf2 functions via generating small amount of ROS [ 21 , 40 ] to up-regulate multiple antioxidants or free radical scavenging capacities [ 21 , 24 , 40 ]; (2) LDR-increased expression of mitochondrial superoxide dismutase [ 41 , 42 ] which may be mediated by LDR-up-regulated Nrf2 transcription function, contributing to the resistance of cardiac cells to DOX; (3) LDR-stimulated mitogen activated protein kinase that turn on cell survival signaling in normal tissues, but not in tumor tissue [ 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“… Based on previous published work from the authors own and others, we assume that LDR may generate small amount of ROS (a) that stimulates cardiac cells to express protective proteins [ 21 – 23 ]; (b) oxidizes Keap1 to disassociate Nrf2 that translocates to nucleus where Nrf2 transcriptionally up-regulates its down-stream antioxidant genes [ 21 , 40 42 ]; (c) stimulates ERK1/2 or ATM/Akt-mediated protective signaling pathways [ 21 , 43 ]; All these possible mechanisms protect mitochondrial damage from DOX, resulting in the protection from DOX-induced cardiac cell death and cardiac toxicity. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATM and p53 are two of the most important genes that are involed in cellular response to radiotherapy and chemotherapy. Yang et al found that the activation of ATM was the initiating event in LDR induced hormesis and adaptive response, and the distinct activation of ATM/AKT/GSK-3β signaling pathway may explain the differential biological effects between lung cancer cells and normal lung epithelial cells (18). Brazina et al showed that the interplay between ATM, p53 and DAxx plays a key role in the regulation of ionizing radiation or genotoxic drug-induced DNA damage (19).…”
Section: Discussionmentioning
confidence: 99%
“…When such research is done, results are often surprising, suggesting, e.g. hormesis at low doses of radiation (Sokolov and Neumann 2015) or different responses to radiation when cancer cells and their normal counterparts are compared (Yang et al 2016). Modeling and systems biology try at the very least to support the 'J shaped' cancer dose response and LNT at the same time (Lou et al 2012;Calabrese 2015).…”
Section: Biological Effects Of Protracted and Acute Radiation Differ mentioning
confidence: 99%